Analysis of the physical and mechanical properties of mortar manufactured from industrial ore waste - Souza, Thalyta Carolina de; Carvalho, Lucas Pinto de; Dias, Fabricio Moura (Technical and Scientific Journal Green Cities, 2025)
The construction industry has contributed significantly to actions that result in environmental and social impacts, among these actions are the use of non-renewable natural resources as raw materials and the generation of waste. As they are non-renewable resources, the exploration of gravel and sand has encouraged the search for sustainable alternatives capable of replacing the use of these materials. This study seeks to evaluate the feasibility of using waste obtained through the mining process as a substitute for natural fine aggregate most frequently used in civil construction. During the process, the waste will be collected and analyzed in relation to its physical and mechanical properties, after which the granulometry test will be carried out so that the waste can be classified according to its granulometric curve. Mortar will be produced in order to carry out axial compression resistance tests and verify the mechanical behavior of the materials. The comparative analysis of the samples reveals that the addition of residue to the material is directly associated with compressive strength. The results reinforce the tendency for resistance to reduce as the percentage of residue in the material increases.